Role of Head Nurses and Services of Nurses as Front Line against Covid-19 Epidemic - Shahzad, Naeem; Amjad, Muhammad Asif; Naz, Tabssum (The journal of contemporary issues in business and government, 2021)
The role of nurses in the health system is like a backbone. The COVID-19 appeared in China in the end of December, 2019 and the epidemic spread around the world. Nurses are risking their lives to work on the front line against the COVID-19. Nurses have always taken risking in performing their duties, but the new epidemic has made their work even more difficult. Nurses are playing a leading role in the fight against Covid-19. The World Health Organization announced the incidence of the coronavirus as an epidemic in March, 2020. The Purpose of the research role of nurses during the Covid-19 pandemic and is to get the front line nurses to known these thought and health issues while talking care of these ablutions.